Comparative in vitro antimicrobial activity of carumonam, a new monocyclic beta-lactam. - Smith, B R (1986)
The antimicrobial activity of carumonam (formerly RO-17-2301), a monocyclic beta-lactam antibiotic, was compared with those of aztreonam, cefotaxime, cefoperazone, ceftazidime, piperacillin, and gentamicin against 455 bacterial isolates. Carumonam did not possess activity against gram-positive cocci and was generally comparable to aztreonam and ceftazidime for most gram-negative bacilli. However, carumonam was the most active beta-lactam against gentamicin-resistant Pseudomonas aeruginosa strains (90% MIC, 8 micrograms/ml).